2006
DOI: 10.1002/jmri.20597
|View full text |Cite
|
Sign up to set email alerts
|

Advanced approach for intraoperative MRI guidance and potential benefit for neurosurgical applications

Abstract: Purpose: To present an advanced approach for intraoperative image guidance in an open 0.5 T MRI and to evaluate its effectiveness for neurosurgical interventions by comparison with a dynamic scan-guided localization technique. Materials and Methods:The built-in scan guidance mode relied on successive interactive MRI scans. The additional advanced mode provided real-time navigation based on reformatted high-quality, intraoperatively acquired MR reference data, allowed multimodal image fusion, and used the succe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 31 publications
(34 reference statements)
0
11
0
Order By: Relevance
“…19,20 Our results of postoperative morbidity regarding language deficits are Other studies evaluated the influence of iMRI resection control on EOR in glioma surgery, including a volumetric analysis of tumor volume, which also showed similar results for EOR and the influence of iMRI. Intraoperative low-field MRI was used by Busse et al, 28 Bohinski et al, 29 and Schneider et al 30 Busse et al 28 reported gross-total glioma resection in 22.7%. Bohinski et al 29 reported that gross total resection (GTR) was enhanced from 47% to 72.5% after iMRI and continued surgery.…”
Section: Intraoperative Mri With Multimodal Navigation and Clinical Omentioning
confidence: 99%
“…19,20 Our results of postoperative morbidity regarding language deficits are Other studies evaluated the influence of iMRI resection control on EOR in glioma surgery, including a volumetric analysis of tumor volume, which also showed similar results for EOR and the influence of iMRI. Intraoperative low-field MRI was used by Busse et al, 28 Bohinski et al, 29 and Schneider et al 30 Busse et al 28 reported gross-total glioma resection in 22.7%. Bohinski et al 29 reported that gross total resection (GTR) was enhanced from 47% to 72.5% after iMRI and continued surgery.…”
Section: Intraoperative Mri With Multimodal Navigation and Clinical Omentioning
confidence: 99%
“…In open scanners with add‐on systems, the virtual navigation scene may be displayed simultaneously with the continuously scanned MR image on two in‐bore monitors (36, 40–42). Such a synchronized view of both visualization modes during a brain biopsy procedure is illustrated in Fig.…”
Section: Principles Of Navigationmentioning
confidence: 99%
“…In a subsequent step, the functional information is then overlaid on the respective intraoperative image (41). Besides the simple landmark or marker‐based techniques, automatic coregistration methods using statistical image measures such as mutual information are also widely available (36, 40–42). Over the past years these techniques have also been successfully applied in various clinical fields.…”
Section: Multimodal and Advanced Navigationmentioning
confidence: 99%
“…Complete tumor resection remains the best treatment option as long as it can be achieved without neurological sequelae. The role of imaging techniques in surgical resection of brain lesions is crucial in every step of surgery: they help planning surgical strategy, provide orientation during surgery, and indicate tumor boundaries and relationships with eloquent areas and vital structures, thus enhancing precision, accuracy, and safety for the patients while maximizing resection [1][2][3][4]. In recent years we are witnessing an increased use of ultrasounds (US) in neurosurgery, as their reliability as an intraoperative tool for tumor detection has been shown in multiple studies [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%